Fault tolerant control of a three‐phase PMSM by limiting the heat of an inter‐turn fault. Issue 2 (9th October 2021) - Foitzik, Simon; Doppelbauer, Martin
Abstract: Inter‐turn faults are most commonly the initial stator winding fault in power trains with Voltage Source Inverters. Without counteractions, these faults can propagate and cause catastrophic failures in safety critical applications like all‐electric aircraft. The propagation of an inter‐turn fault can be reduced, by limiting the local temperature at the fault. In this article, a fault tolerant control scheme is designed and validated, which reduces the heat of an inter‐turn fault by a controlled adaption of the operating point. The control strategy utilizes the hyperbolas of constant torque and the controller design is based on a linear time‐invariant system description. A machine learning regression is used for the online heat estimation and a 3D lumped‐parameter model to evaluate the thermal effectiveness. To test the control scheme, an inter‐turn fault is actively switched, which generates the local heat equal to 13 % of the overall stator copper losses. The control scheme adopts the operating point within 30 electric periods, which reduces the generated heat of the inter‐turn fault by 70 % . This causes a temperature reduction at the fault locally from 367 °C to 175 °C, which extends the approximated insulation life from 30 s to 5000 h.